Relationship of low muscle mass and obesity with physical function in community dwelling older adults: Results from the Nagahama study. (May 2020) - Tanaka, Masayo; Ikezoe, Tome; Ichihashi, Noriaki; Tabara, Yasuharu; Nakayama, Takeo; Takahashi, Yoshimitsu; Matsuda, Fumihiko; Tsuboyama, Tadao; ,
Highlights: Low muscle mass and obesity negatively influence balance and walking abilities. Gender difference exists in relationship between obesity and muscle strength. Association between obesity and physical function differs depending on muscle mass. Abstract: Aim: Relationships of low muscle mass and obesity with physical function were investigated in older adults. Methods: The participants were 1922 community dwelling persons aged 60 years or older (67.7 ± 5.2 years old, 643 men and 1279 women). One-leg standing time, knee extensor muscle strength, and maximum walking speed were assessed. Muscle mass was evaluated using the bioelectrical impedance analysis (BIA) method, and skeletal mass index (SMI) was determined. For the obesity index, waist circumference with a stronger association with visceral fat was used. Participants were classified into the following four groups based on standard values of waist circumference and SMI: non-obese low-SMI, obese low-SMI, non-obese normal-SMI, and obese normal-SMI. Results: By two-way analysis of variance (obesity × SMI), the main effects of waist circumference and muscle mass were noted in the one-leg standing time. The maximum walking speed was higher in the non-obese than the obese group, and in the normal than the low SMI group. In the muscle strength, a main effect was noted only in the muscle mass of women. An interaction was noted in men and significant differences were detected between all combinations except between the non-obese low SMI and obese low SMI groups. Conclusion: Low muscle mass and obesity negatively influence balance and walking abilities. However, the influence of low muscle mass and obesity on muscle strength were different between the sexes. In men, the relationship between obesity and muscle strength would be different depending on whether muscle mass is retained.